2022
DOI: 10.3758/s13415-022-01016-w
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and behavioral correlates of cannabis use disorder

Abstract: Current research indicates deficits in cognitive function together with widespread changes in brain activity following long-term cannabis use. In particular, cannabis use has been associated with excessive spectral power of the alpha rhythm (8–12 Hz), which is also known to be modulated during attentional states. Recent neuroimaging studies have linked heavy cannabis use with structural and metabolic changes in the brain; however, the functional consequences of these changes are still not fully characterized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Haegens et al found that the alpha-band activity increased in the sensorimotor cortex ipsilateral to the engaged hand in a somatosensory working memory task, while it decreased in the contralateral hemisphere [73]. Furthermore, the stronger 8.0 Hz neuronal inhibition (greater desynchronisation) in MIEC condition than that of MIEO in both ipsi-and contralateral cortices (see Figure 6) suggests an interruption in attentional processing caused by opening the eyes [74]. The pre-movement 9.5 Hz rhythm desynchronization observed in the MIEC condition (Figure 5) may be explained by the notion that pre-stimulus alpha oscillatory activity modulates the subsequent processing of visual and somatosensory stimuli [72].…”
Section: Physiological Interpretation Of the Findingsmentioning
confidence: 97%
“…Haegens et al found that the alpha-band activity increased in the sensorimotor cortex ipsilateral to the engaged hand in a somatosensory working memory task, while it decreased in the contralateral hemisphere [73]. Furthermore, the stronger 8.0 Hz neuronal inhibition (greater desynchronisation) in MIEC condition than that of MIEO in both ipsi-and contralateral cortices (see Figure 6) suggests an interruption in attentional processing caused by opening the eyes [74]. The pre-movement 9.5 Hz rhythm desynchronization observed in the MIEC condition (Figure 5) may be explained by the notion that pre-stimulus alpha oscillatory activity modulates the subsequent processing of visual and somatosensory stimuli [72].…”
Section: Physiological Interpretation Of the Findingsmentioning
confidence: 97%
“…An extensive literature has demonstrated that chronic cannabis use is harmful for the pulmonary and respiratory system [ 10 , 11 ], the cardiovascular system [ 12 , 13 ], as well as the central nervous system (CNS) [ 14 , 15 , 16 , 17 , 18 ], especially if used in adolescence [ 19 , 20 , 21 , 22 , 23 ]. Moreover, the efforts made throughout the years by companies and criminal organizations to make cannabis more potent have led to very high THC levels in weed strains, deeply influencing consumption patterns and long-term use outcomes [ 24 ].…”
Section: Introductionmentioning
confidence: 99%